Impact of Pt. Central Proteinaprima Customer Relationship Management towards Customer Loyalty In Sidoarjo Area - Ivandy Santoso (iBuss Management, 2015)
Customer Relationship Management is considered as an important factor that can impact customer loyalty in purchasing a product. In Sidoarjo, PT. Central Proteinaprima, a fish feed company, also competes with other companies to attract customer loyalty. This research is conducted with the aim to find out the effect of  customer relationship management on customer loyalty. The data was gathered  using  simple  random  sampling  by  distributing  questionnaires  to  150  respondents  in Sidoarjo.  The data was analyzed by using Multiple Linear Regression Analysis. The result  shows that customer relationship management simultaneously has significant  impact on customer loyalty. Furthermore, the result also shows that  interaction management, relationship development, quality of services, and behavior of employees have significant impact toward customer loyalty. Keywords: Customer Relationship Management, Customer Loyalty